Thermal and Environmental Design for Human Comfort in Japanese-Designed Architecture in Thailand - Piyarat Nanta; Ravij Kuanprasert (Environment-Behaviour Proceedings Journal, 2023)
These multiple case studies investigate thermal and environmental architectural details unique to the Japanese-designed educational facilities in Thailand, namely [1] King Mongkut Institute of Technology Ladkrabang 's Auditorium and Memorial Hall, [2] Lecture Halls, [3] Kasetsart University's Central Laboratory, [4] Thammasat University's Institute of Japanese Studies, and [5] Ministry of Natural Resources and Environment’s Research Center. Data sources include archival records, site surveys, and interviews. The findings reveal various design strategies, such as double-layer walls, complex roofing design, specific orientation, and water features that contemporary sustainable building designs may adopt to increase thermal comfort while reducing energy consumption.
Keywords: Building Energy and Comfort Optimization; Architectural and Urban Studies